Gamification's role as an assessment and learning tool in education - Sanmugam, Mageswaran (2015)
Gemificaticn is a new and upcoming trend that is predicted by many to further enhance the field of educational technology in the new millennium. The use of gamification has fared well in the coorperate world and is gradually transcending into the educational arena, The usage of game elements such as points. badges and leaderboard can assist in keeping the students not only motivated but also engaged to the leaching and learning process in the school, As learning and assessment come hand in hand as a knowledge acquiring process in a classroom, therefore it should be identified whether gamification can be truly utulized is via the form of an assessment and learning tool in the teaching and learning process. This paper will discuss about the repercussions of using gamefication as an assessment and learning tool based on the review of severel studies.